APPLICATION OF PLAY-BASED LEARNING IN BIPA LEARNING:STUDY IN BAKONG PITTAYA SCHOOL, PATTANI-THAILAND - Fendy Yogha Pratama; Halimatussakdiah Halimatussakdiah; Usman Toktayong (Universitas Negeri Medan, 2020)
Abstract: The Implementation of Play-Based Learning on BIPA Learning: Study in the Elementary School of Bakong Pittaya, Pattani-Thailand. The purpose of this Classroom Action Research is to improve students' BIPA learning outcomes, especially vocabulary achievement and enjoyment level in class by implementing Play-Based Learning. The subjects are 40 students of Bakong Pittaya School, Pattani-Thailand. The result of the study showed that there was an improvement of students' vocabulary achievement and enjoyment .Keywords : Play-Based learning, BIPA, elementary school, ThailandAbstract: Penerapan Play-Based Learning pada Pembelajaran BIPA: Studi di Sekolah Dasar Bakong Pittaya, Pattani-Thailand. Tujuan dari Penelitian Tindakan Kelas ini adalah untuk meningkatkan kemampuan luaran pembelajaran BIPA, khususnya penguasaan kosakata dan rasa senang dalam kelas dengan menerapkan pembelajaran berbasis permainan. Subjek pada penelitian ini adalah 40 siswa sekolah dasar Bakong Pittaya School, Pattani-Thailand. Hasil penelitian menunjukkan bahwa terdapat peningkatan pada penguasaan kosakata siswa dan rasa senang. Keywords: Play-Based learning, BIPA, sekolah dasar, Thailand